Fourier transformation infrared (FTIR) spectroscopy of human saliva as a novel approach for detection dengue virus infection in children - Eko Suhartono; Iskandar Iskandar; Edi Hartoyo (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2020)
No abstract